2017
DOI: 10.4049/jimmunol.1601894
|View full text |Cite
|
Sign up to set email alerts
|

An Infectious Disease–Associated Il12b Polymorphism Regulates IL-12/23 p40 Transcription Involving Poly(ADP-Ribose) Polymerase 1

Abstract: IL-12 and IL-23 are important host defense factors produced by APCs against certain intracellular and extracellular pathogens. Their dysregulation has also been implicated in several autoimmune diseases. The nucleotide polymorphism in the promoter region of (rs41292470 consisting of the long or short allele) encoding the shared subunit of IL-12 and IL-23, p40, has been reported to associate with susceptibility to infectious diseases and autoimmune disorders. How these genetic variants impact expression at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The primers are shown in Supplementary Table 4. A DNA pulldown assay was performed as described previously 22 using Caco-2 cells. For liquid chromatography-tandem mass spectrometry (LC-MS/MS) analyses, a Q-Exactive mass spectrometer (Thermo 588 Finnigan, San Jose, CA, USA) coupled with an Easy-nLC1000 HPLC system 589 (Thermo Fisher, San Jose, CA, USA) was used as described previously.…”
Section: Dna Pulldown and Mass Spectrometry (Ms)mentioning
confidence: 99%
“…The primers are shown in Supplementary Table 4. A DNA pulldown assay was performed as described previously 22 using Caco-2 cells. For liquid chromatography-tandem mass spectrometry (LC-MS/MS) analyses, a Q-Exactive mass spectrometer (Thermo 588 Finnigan, San Jose, CA, USA) coupled with an Easy-nLC1000 HPLC system 589 (Thermo Fisher, San Jose, CA, USA) was used as described previously.…”
Section: Dna Pulldown and Mass Spectrometry (Ms)mentioning
confidence: 99%
“…Furthermore, the inhibition of ADP-ribosylation with PJ34 attenuated high glucose-induced macrophage calcification by inhibiting Runx2 expression and enhancing M2 differentiation. Moreover, IFN-γ and LPS/IFN-γ triggered the transcription of the IL12b gene encoding p40, a subunit of IL-12 and IL-23 in human peripheral blood mononuclear cells (PBMC), as well as in THP1-derived macrophages, in a PARP1-dependent fashion [85]. The enzyme recruitment to the IL12b locus resulted in promoter activation and p40 expression, whereas PARP1 silencing with shRNA resulted in the considerable reduction of p40 expression.…”
Section: The Role Of Parp1 In Stat1/3 Signaling-implications For Viramentioning
confidence: 99%
“…PARP1 regulates the transcription of IL10 in an allele-dependent way in macrophages engulfing apoptotic cells, but not upon LPS stimulation. It binds to -1082G>A alleles in the gene promoter, represses cytokine expression, and, thus, defines allele-dependent susceptibility to inflammatory pathology [85]. Furthermore, in cancer cells, PARP1 represses the anti-inflammatory cytokines IL10 and IL13 as well as PD-L1.…”
Section: Parp1 In Anti-inflammatory Polarization Of Macrophages-insigmentioning
confidence: 99%
“…Among these, the deglycosylated peptide with the site of N303 from IL12B was up-regulated by 7.5 times, and this has been reported previously. 47,48 We also found that the two deglycosylated peptides with the site of N183 or N267 from intercellular adhesion molecule 1 (ICAM1) were up-regulated by 2.1 and 2.5 times, respectively. ICAM1 is a known cellsurface glycoprotein involved in leukocyte adhesion and is often up-regulated under inflammatory conditions.…”
Section: ■ Experimental Sectionmentioning
confidence: 88%